Akibat Hukum Perjanjian Sewa Menyewa Alat Berat yang dipergunakan Untuk Melakukan Perbuatan Melawan Hukum - Brian Hariadi; Marjon, Dahlil; Yasniwati, Yasniwati (UNES Law Review, 2024)
During activities, mining entrepreneurs often rent heavy equipment in the form of excavators from other entrepreneurs. It often happens that rented items are used to commit crimes, which leads to the confiscation of rented items as evidence. Therefore, renting entrepreneurs will suffer economic losses. This raises the legal question of how to protect tenants in this case. To answer this question, we need to do a study. This study is a normative legal study, which raises three (three) legal issues, namely (1) examining the reasons for the confiscated heavy equipment by law enforcement departments; (2) examining the legal consequences of confiscated on third parties renting heavy equipment; and (3) examining the forms of legal protection for third parties renting heavy equipment. The study shows that, first of all, the reason for the confiscation is to let investigators have evidence of the crime. Secondly, the legal consequence of confiscation on third parties is the inability to use their heavy equipment to earn income, resulting in delayed payment of credit for the purchase of confiscated goods. Third, the third party is protected by the laws of Article 206, Article 227-228 R.Bg and Article 195 (6) HIR. The third party has the right to make resistance efforts (derden verzet) before the case is adjudicated.